The effects of baseball bat mass properties on swing mechanics, ground reaction forces, and swing timing - Laughlin, W. A.; Fleisig, G. S.; Aune, K. T.; Diffendaffer, A. Z. (Sports Biomechanics, 2016)
Swing trajectory and ground reaction forces (GRF) of 30 collegiate baseball batters hitting a pitched ball were compared between a standard bat, a bat with extra weight about its barrel, and a bat with extra weight in its handle. It was hypothesised that when compared to a standard bat, only a handle-weighted bat would produce equivalent bat kinematics. It was also hypothesised that hitters would not produce equivalent GRFs for each weighted bat, but would maintain equivalent timing when compared to a standard bat. Data were collected utilising a 500 Hz motion capture system and 1,000 Hz force plate system. Data between bats were considered equivalent when the 95% confidence interval of the difference was contained entirely within ±5% of the standard bat mean value. The handle-weighted bat had equivalent kinematics, whereas the barrel-weighted bat did not. Both weighted bats had equivalent peak GRF variables. Neither weighted bat maintained equivalence in the timing of bat kinematics and some peak GRFs. The ability to maintain swing kinematics with a handle-weighted bat may have implications for swing training and warm-up. However, altered timings of kinematics and kinetics require further research to understand the implications on returning to a conventionally weighted bat.